Some Bronze Plaques with Repoussé Decoration in the Danish National Museum. An Investigation into an Early Etruscan Style of Decorations - Salskov Roberts, Helle (1963)
ersch. 1964; nimmt anatolisch-nordsyr. Einflüsse an.